2021
DOI: 10.3390/joitmc7020110
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local Economic Conditions on Start-Ups and Local Open Innovation System

Abstract: The development of start-ups is a driving force of the local and regional economy. Therefore, it should be in the interest of municipal authorities to take actions for their organizational and resource support. In the conditions of limited public resources, however, it is a difficult and multifaceted task. Therefore, in this article, the authors attempt to determine the influence of local conditions on the establishment of start-ups. As a natural environment for the development of this type of entrepreneurship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 98 publications
1
12
0
Order By: Relevance
“…Entrepreneurial companies play an essential role in economic development and economic fluctuations affect DEs. Jonek-Kowalska and Wolniak (2021) confirmed that there is a significant impact of the economic conditions on emerging companies. Furthermore, a lower significant role of business incubators in stimulating start-ups was observed.…”
Section: Resultsmentioning
confidence: 72%
“…Entrepreneurial companies play an essential role in economic development and economic fluctuations affect DEs. Jonek-Kowalska and Wolniak (2021) confirmed that there is a significant impact of the economic conditions on emerging companies. Furthermore, a lower significant role of business incubators in stimulating start-ups was observed.…”
Section: Resultsmentioning
confidence: 72%
“…An important aspect from the point of view of the functioning of the brand and the implementation of innovative solutions is direct cooperation with its customers. This approach is the basis for the concept of open innovation [47][48][49]. Research shows that 93% of companies do not allow users to make decisions when changing the visual communication of their systems.…”
Section: Discussionmentioning
confidence: 99%
“…Start-ups, i.e. companies in the beginning of its creation, are driving forces for innovation and growth [56], and have a certain ability and freedom to modernise quickly, with access to funding from many different sources [57]. However, they do not necessarily have access to the end customer, condition required to bring the product to market, enabling a technology to scale [58].…”
Section: The Creation Of Start-upsmentioning
confidence: 99%
“…Start-ups are the best display of enterprise venture and innovation. They are differentiated from other commercial firms by dynamic business evolution mainly accomplished by adopting modern technologies, such as information and communication [57].…”
Section: The Creation Of Start-upsmentioning
confidence: 99%
See 1 more Smart Citation